Influence of particle size of crude olive cake on in vitro ruminal fermentation and gas production kinectics - Marcos C.N.; Chávez S.; Blas C.; Molina Alcaide E.; Ranilla M.J.; Carro M.D. (Innovation for sustainability in sheep and goats, 2019)
By-products of olive oil industry can be used in ruminants feeding, but their nutritive value can be affected by the processing method. The aim of this research was to estimate in vitro the nutritive value of four samples of crude olive cake (COC) with different particle size obtained during the drying process from the same trommel at different stages of the screening procedure. Particles size was greater than 3 mm (COC3), 2 mm (COC2) and 1 mm (COC1) or smaller than 1 mm (COC0). Alfalfa hay and barley straw were included in the study for comparative purposes. Chemical composition was analysed in all samples. Gas production kinetics was determined in 144-h in vitro incubations with sheep rumen fluid as inoculum, and fermentation parameters and in vitro dry matter digestibility (IVDMD) were analysed after 24 h of incubation. COC3 and COC0 samples had lower contents of neutral detergent fibre (NDF; 415 and 391 g/kg DM), but greater crude protein (96.6 and 114 g/kg DM) and ether extract (220 and 242 g/kg DM) contents, than COC2 and COC3 (627 and 624; 42.4 and 48.7; 102 and 124 g/kg DM, respectively). IVDMD of COC samples ranged from 39.4 to 58.7%, and was lower than that for alfalfa hay (67.5%) for all samples, but greater than that for barley straw (42.4%) for COC0 and COC3 samples. COC3 and COC0 samples had greater (P<0.05) potential gas production (103 and 66.2 ml/g DM, respectively) and total volatile fatty acids production (608 and 600 μmol, respectively) than COC2 and COC1, but values were lower than those for alfalfa hay (202 ml/g DM and 1023 μmol, respectively) and barley straw (198 ml/g DM and 733 μmol). The results indicate that decreasing particle size to <1 mm increased the fermentation potential of COC, but its nutritive value was still slightly lower than that of barley straw. The similar quality observed for COC3 and COC0 samples was attributed to the high sugar content of COC3 samples.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)